Why not promote promotion for green consumption?: The controversial role of regulatory focus. Issue 5 (13th August 2018) - Codini, Anna Paola; Miniero, Giulia; Bonera, Michelle
Abstract : Purpose: The purpose of this paper is to empirically test the effects of regulatory focus (RF) orientation (promotion/prevention) on decisions to purchase green products. The two experimental studies conducted aimed to test whether individuals in a prevention (promotion) state were more (or less) inclined to buy green products. Design/methodology/approach: To test the effect of RF on green and non-green consumption, the authors carried out two experimental studies (one considering a service – car sharing – the other a physical product – a laundry detergent). The studies are 2 (RF: prevention vs promotion) × 2 (product type: green vs non-green) between factorial design involving 196 and 92 participants, respectively. Findings: Promotion-focus has a powerful influence on green consumption. In both studies, individuals with a promotion focus seemed to be more inclined to buy green products as opposed to individuals in a prevention state. Research limitations/implications: The main limitations of this study first relate to the results of the two experiments. Even though both studies showed that promotion-focused rather than prevention-focused individuals are more inclined to buy green products, the differences between the two orientations in green condition are not statistically significant. As a result, the studies cannot determine whether to reject or accept the two main hypothesis. Social implications: This paper provides some preliminary indications that could be useful to encourage consumers to adopt "green" styles of consumption. Focusing on an individual's RF is a useful strategy to induce them to change their consumption choices abruptly. Relying more on a "promotion" rather than a "prevention" focus, individuals would be compelled to take immediate responsible behavior. Originality/value: This paper aims to fill the gap on the role of RF in green consumption. Contrary to the accepted idea that a prevention state is more compatible with consumer ethics than promotion state, the studies showed the controversial role assumed by a prevention state in green consumption.